Trace metals in aquatic systems - Mason, Robert P. (Robert Peter), 1956- (Hoboken, N.J. : John Wiley & Sons Inc., 2013)
"The textbooks that currently exist do not deal with this particular subject in a comprehensive fashion, and therefore this book is being proposed to full this gap"--
Machine generated contents note: Chapter 1: Introduction 1.1 A Historical Background to Metal Aquatic Chemistry 1.2. Historical Problems with Metal Measurements in Environmental Media 1.3 Recent Advances in Aquatic Metal Analysis Chapter 2: An Introduction to the Cycling of Metals in the Biosphere 2.1 The Hydrologic Cycle 2.2 An Introduction to the Global Cycling of Trace Metals 2.3 Global Cycles of Some Important Trace Metals 2.4 Chapter Summary - Main Points Chapter 3: Chemical Thermodynamics and Metal(loid) Complexation in Natural Waters 3.1 Thermodynamic Background for Understanding Trace Metal(loid) Complexation 3.2 Bonding, Electronic Configuration and Complex Formation 3.3 Complexation of Metals in Solution 3.4 Trace Metal Interactions with the Solid Phase 3.5. Redox Transformations and Thermodynamic Calculations 3.6. Chapter Summary Chapter 4: Modeling Approaches to Estimating Speciation and Interactions in Aqueous Systems 4.1 Introduction 4.2 The Underlying Basis and Application of Chemical Equilibrium Models 4.3 Adsorption Modeling 4.4 Modeling Interactions between Cations and Organic Matter and Inorganic Surfaces 4.5 Modeling Redox Transformations 4.6 Modeling the Kinetics of Reactions 4.7 Incorporating Kinetics and Thermodynamics into Fate and Transport Modeling 4.8. Chapter Summary Chapter 5: Metal(loid)s in the Atmosphere and their Inputs to Surface Waters 5.1 Introduction 5.2 Atmospheric Transport and Deposition 5.3 Atmospheric Chemistry and Surface Water Photochemistry of Metals 5.4 Solubilization of Aerosol Metal(loid)s in Natural Waters 5.5 Focus Topics 5.6 Inputs of Atmospheric Metals to the Biosphere 5.7 Chapter Summary Chapter 6: Trace Metal(loid)s in Marine Waters 6.1 Introduction 6.2 Metal(loid) Partitioning in Coastal and Open Ocean Waters 6.3 Metals in Coastal and Offshore Sediments 6.4 Metal Distributions in Open Ocean Waters 6.5 Chapter Summary Chapter 7: Trace Metals in Freshwater 7.1 Overview of Metal cycling in Freshwaters 7.2 Trace Element Cycling in Lakes 7.3 Trace Elements in Rivers and Groundwater 7.4 Human Activities and Their Impact on Trace metal(loid) Concentration in Drinking Water and Receiving Waters 7.5 Metal Stable Isotopes and Their Uses 7.6 Chapter Summary Chapter 8: Trace Metals and Organisms: Essential and Toxic Metals, Organometallics, Microbial Processes and Metal Bioaccumulation 8.1 Introduction 8.2 Mechanisms of Metal Accumulation by Microorganisms 8.3 Essential Trace Metals 8.4 Organometallic Compounds and Microbial Transformation of Metals 8.5 Bioavailability and Bioaccumulation 8.6 Chapter Summary Index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Trace elements -- Analysis; Water -- Analysis; Water chemistry; Electronic books